Unusual small bowel metastatic localization in a castration-resistant prostate cancer patient. (December 2014) - Maines, Francesca; Caffo, Orazio; Veccia, Antonello; Galligioni, Enzo
The introduction of docetaxel into clinical practice and the more recent availability of other active therapeutic options, such as cabazitaxel, abiraterone acetate, enzalutamide and radium-223, have significantly improved the clinical outcomes of patients affected by castration-resistant prostate cancer (CRPC). Bone and nodes metastases are usually the first presentation of advanced disease, but the improvement in overall survival and the greater use of imaging techniques for restaging of metastatic CRPC patients have led to a previously unexpected clinical scenario characterized by an increased incidence of visceral metastases not only in the liver and lungs, but also in atypical sites such as the brain or gastrointestinal tract. We describe a rare case of CRPC metastasizing to the small bowel with particular endoscopic and radiographic findings.